Anesthetic management of laparoscopically assisted fetoscopic surgery to correct spina bifida - D. N. Nikonov; A. V. Filippov; A. V. Yakovlev; A. N. Taits; V. A. Reznik; D. O. Ivanov (Вестник анестезиологии и реаниматологии)
Introduction. The growing incidence of intrauterine pathology in the fetus at the present stage dictates the need to develop and improve intrauterine surgical correction of defects in the fetus. Myelomeningocele (SPINA BIFIDA) is the most common and severe neural tube defect in the fetus, the severity of the neurological deficit is determined by the level of location and extent of the anomaly. By uniting doctors of various specialties (obstetricians-gynecologists, neonatologists, surgeons, anesthesiologists-resuscitators), the Clinic of the St. Petersburg State Pediatric Medical University effectively introduces methods of prenatal surgery.The objective was to demonstrate by clinical example the experience of successful fetoscopic correction of myeloneningocele to reduce maternal risks and injuries, to reduce risks aimed at protecting the tissues of the spinal cord of the fetus, as well as to reduce the need for postpartum correction of the defect in the fetus, to improve prognosis and risks of subsequent disability.Materials and methods. The article presents the first successful experience of minimally invasive laparoscopic correction of myelomeningocele in the fetus with the participation of the multidisciplinary team and the features of anesthesiological support of the method.Conclusion. Laparoscopic access, together with the optimal choice of anesthetic management in fetal surgery, allows not only to successfully correct the defect in myelomeningocele in the fetus, but also to significantly minimize and reduce the risks of injury to the mother, and also reduces the need for postpartum surgical treatment and reduce disability. Accumulation and improvement of experience, a multidisciplinary approach is the key to successful correction of intrauterine fetal pathology.